2013
DOI: 10.1038/srep02553
|View full text |Cite
|
Sign up to set email alerts
|

The flavonoid apigenin improves glucose tolerance through inhibition of microRNA maturation in miRNA103 transgenic mice

Abstract: Polyphenols are representative bioactive substances with diverse biological effects. Here, we show that apigenin, a flavonoid, has suppressive effects on microRNA (miRNA) function. The effects were mediated by impaired maturation of a subset of miRNAs, probably through inhibition of the phosphorylation of TRBP, a component of miRNA-generating complexes via impaired mitogen-activated protein kinase (MAPK) Erk activation. While glucose intolerance was observed in miRNA103 (miR103)-overexpressing transgenic mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 36 publications
3
59
0
Order By: Relevance
“…It was reported that TRBP phosphorylation enhanced the maturation of miRNAs through stabilization of the miRNA-generating complex (Paroo et al, 2009). Administration of apigenin suppressed expression of miR-103 in miR-103 transgenic mice by inhibiting TRBP phosphorylation (Ohno et al, 2013). On the other hand, polyphenols may bind to miRNAs directly.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that TRBP phosphorylation enhanced the maturation of miRNAs through stabilization of the miRNA-generating complex (Paroo et al, 2009). Administration of apigenin suppressed expression of miR-103 in miR-103 transgenic mice by inhibiting TRBP phosphorylation (Ohno et al, 2013). On the other hand, polyphenols may bind to miRNAs directly.…”
Section: Discussionmentioning
confidence: 98%
“…The administration of this flavonoid at the dose of 4 mg/kg bw/day after 1 week determined the reduction of blood GLU levels and demonstrated an efficient protection on liver and kidney. Moreover, apigenin improved GLU tolerance through inhibition of microRNA maturation in miRNA103 transgenic mice 25 . Escande et al 26 described the ability of apigenin and quercetin to increase intracellular nicotinamide adenine dinucleotide (NAD + ) levels by the inhibition of enzyme CD38.…”
Section: Discussionmentioning
confidence: 99%
“…A mixture of 1.5 ml of 0.25 mm DPPH solution in ethanol and 12 ml of CD extract at different concentrations was prepared and allowed to reach a steady state at 25 C for 30 min. The bleaching of DPPH was measured at 517 nm with UV-vis Jenway 6003 spectrophotometer (Milan, Italy).…”
Section: Dpph Radical Scavenging Activity Assaymentioning
confidence: 99%
“…This compound has been reported to have anti-inflammatory, antioxidant and anti-carcinogenic properties . Apigenin has been reported to improve glucose tolerance through inhibition of microRNA maturation in miRNA103 transgenic mice (Ohno et al, 2013). Detailed investigation related to antidiabetic potential of apigenin still remains elusive.…”
Section: Science Publicationsmentioning
confidence: 99%
“…Apigenin was dissolved in water containing 0.1% v/v Dimethyl Sulfoxide (DMSO) for animal treatment according to the earlier report (Ohno et al, 2013). Absorption and elimination phase of apigenin via oral route is very slow and biological t 1/2 of apigenin is 91.8 h. As metabolism is slow, apigenin has general tendency to accumulate in tissue after oral administration.…”
Section: Experimental Designmentioning
confidence: 99%